2015
DOI: 10.1371/journal.pone.0139913
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Validation of a Multi-Kinect v2 Instrumented 10-Meter Walkway for Quantitative Gait Assessments

Abstract: Walking ability is frequently assessed with the 10-meter walking test (10MWT), which may be instrumented with multiple Kinect v2 sensors to complement the typical stopwatch-based time to walk 10 meters with quantitative gait information derived from Kinect’s 3D body point’s time series. The current study aimed to evaluate a multi-Kinect v2 set-up for quantitative gait assessments during the 10MWT against a gold-standard motion-registration system by determining between-systems agreement for body point’s time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
153
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 32 publications
9
153
3
4
Order By: Relevance
“…Kinect V1 and V2 have been proposed for the quantification of motor symptoms, for example in posturography [3, 4], gait analysis [57] and quantification of hypokinesia in Parkinson’s disease [2]. Gait analysis with multi-camera [8] or single-camera setup [5, 6] in healthy subjects suggested high accuracy for gait speed, stride length, stride time but lower accuracy for other parameters like stride width or speed variability. The accuracy of functional movement parameters of standing balance seemed to depend on observed movement amplitude [3, 4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinect V1 and V2 have been proposed for the quantification of motor symptoms, for example in posturography [3, 4], gait analysis [57] and quantification of hypokinesia in Parkinson’s disease [2]. Gait analysis with multi-camera [8] or single-camera setup [5, 6] in healthy subjects suggested high accuracy for gait speed, stride length, stride time but lower accuracy for other parameters like stride width or speed variability. The accuracy of functional movement parameters of standing balance seemed to depend on observed movement amplitude [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis was confined to trunk landmarks in these studies. Comprehensive studies on Kinect V2 landmark movement accuracy [8, 9] pointed to differences in signal accuracy with landmark location and the direction of movements performed. Importantly, retest reliability was not generally lower with Kinect compared to other motion tracking systems.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple Kinect V2 setups has already been used in different research (e.g. [Geerse et al 2015]), it seems they ignore the possibility of interference between multiple sensors. Altough a detailed study of working principle of Kinect V2 suggests otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several studies found an apparent interference between two Kinect sensors in the same generation; none of them evaluated or discussed interference between Kinect sensors and golden standard motion capture systems [9,19,2330]. …”
Section: Introductionmentioning
confidence: 99%